Enhancing OBE performance for civil engineering students with CDIO implementation / Nurul Aishah Abd Rahman, Muhammad Isha Ismail and Mohd Fakri Muda - Abd Rahman, Nurul Aishah; Ismail, Muhammad Isha; Muda, Mohd Fakri (2015)
This paper generally introduces Conceive-Design-Implement-Operate (CDIO) implementation in Faculty of Civil Engineering, UiTM Pahang. CDIO based teaching method is a new educational framework which organically integrates teacher's research based teaching and student's research based study in class. It emphasizes on teacher and student's leading role while simultaneously cultivates student's learning interest and thinking as well as his capability of analyzing and solving problems. This paper highlights the CDIO process framework as supporting documents to enhance Outcome Based Education (OBE) results towards sustainable development in educations. This approach helps to systematically facilitate students-centered learning to improve, embed and monitor all skills required by civil engineering students. The required skills can be indicated using the standard rubrics developed based on the CDIO approach. The rubrics were prepared based on the communication, teamwork and critical thinking skills aligned with the required PO's attainment. It is important to continuously implement this framework and monitor its effects to assess the performance and improvement gained from the initiative. An educator was also accumulating CDIO knowledge in a workshop organized by faculty as a preparation to achieve our vision. The study found that the application of CDIO in a classroom positively enhanced the P02, P04, P07 and P08 assessments. However the P03 assessment was found to be negative due to the students' poor thinking style while solving the problems.